Age within schoolyear and attention-deficit hyperactivity disorder in Scotland and Wales - Michael Fleming; Amrita Bandyopadhyay; James S. McLay; David Clark; Albert King; Daniel F. Mackay; Ronan A. Lyons; Kapil Sayal; Sinead Brophy; Jill P. Pell (BMC Public Health, 2022)
Abstract Background Previous studies suggest an association between age within schoolyear and attention-deficit hyperactivity disorder (ADHD). Scotland and Wales have different school entry cut-off dates (six months apart) and policies on holding back children. We aim to investigate the association between relative age and treated attention deficit hyperactivity disorder (ADHD) in two countries, accounting for held-back children. Methods Routine education and health records of 1,063,256 primary and secondary schoolchildren in Scotland (2009–2013) and Wales (2009–2016) were linked. Logistic regression was used to examine the relationships between age within schoolyear and treated ADHD, adjusting for child, maternity and obstetric confounders. Results Amongst children in their expected school year, 8,721 (0.87%) had treated ADHD (Scotland 0.84%; Wales 0.96%). In Wales, ADHD increased with decreasing age (youngest quartile, adjusted OR 1.32, 95% CI 1.19–1.46) but, in Scotland, it did not differ between the youngest and oldest quartiles. Including held-back children in analysis of their expected year, the overall prevalence of treated ADHD was 0.93%, and increased across age quartiles in both countries. More children were held back in Scotland (57,979; 7.66%) than Wales (2,401; 0.78%). Held-back children were more likely to have treated ADHD (Scotland OR 2.18, 95% CI 2.01–2.36; Wales OR 1.70, 95% CI 1.21–2.31) and 81.18% of held-back children would have been in the youngest quartile of their expected year. Conclusions Children younger within schoolyear are more likely to be treated for ADHD, suggesting immaturity may influence diagnosis. However, these children are more likely to be held back in countries that permit flexibility, attenuating the relative age effect.